An analysis of family size preference and attitudes toward family planning in selected areas in the Philippines - Pacheco, Antonio Romulo 1944- (Quezon City Population Institute, University of the Philippines Diliman, 1968)
This study has been done primarily with the objectives of determining whether there has been a change in the desired family size of married women at least between the younger and the older generations; to determine the extent in which different demographic and socio-economic variables affect the desired family size; and to discover the extent of the knowledge and effectiveness of the methods of contraception which these married women know in order to achieve the precariously held family size desired.

The data utilized for this study are the results of the four fertility surveys conducted by the U.P. Statistical Center, Institute of Hygiene and the Population Institute from the year 1963 to 1966.

Indexes of dissimilarity and X² (Chi-Square) tests have been used to compare the compositional distribution of the sample results with those of the census results, for the former; and to determine the relationship existing between family size preference and the different demographic and socio-economic variables considered, for the latter. Standardization technique was also used to control the effect of the differences in age and socio-economic composition of married women in the sample areas as they affect the number of preferred children.
Thesis
Keywords: Family size; Birth control; Contraceptives